ROLE OF REDOX CONDITIONS IN THE ACCUMULATION OF EU2+, YB2+, AND SM2+ IN PETROLEUM OILS - Balashov Y.A.; Tsoy K.S. (My University, 1989)
Following its conversion from Eu3+ to Eu2+ under reducing conditions that result when an excess of organic matter is present, europium migrates in sedimentary rock at rates higher than the other rare earth elements. It tends to accumulate preferentially in coal, the kerogen of blackschist associations, and the phosphate of bone detritus. Yb and Sm can also change valence, but this occurs under more strongly reducing conditions, and so far there is no evidence of their migration as Ye2+ and Sm2+ under natural conditions.